DETERMINATION OF DENTAL AGE OF 10-13 YEAR-OLD CHILDREN OF THE CARPATHIAN REGION OF UKRAINE BY THE CAMERIERE METHOD IN COMPARISON WITH THEIR CHRONOLOGICAL AGE - V.F. Makieyev; O.O. Isakova (Ukrainian Medical Stomatological Academy, 2019)
Purpose:  to evaluate the chronological and dental age of children in Lviv and the Lviv region aged 10-13 years with the help of the modified formula Cameriere.  Methods. Оrthopantomograms  46 children (26 boys and 20 girls) aged 10-13 years from Lviv and Lviv region have been used for this study. A questionnaire was developed for the submission of individual patient data and a standardized format for making their indicators derived from orthopantomograms (OPG). The examination of the area of the lower seven teeth on the left was done using the Cameriere method and the age of the child was evaluated, which was further compared with the chronological age.  Results.The obtained results of the study showed a high accuracy and reliability of the estimation of dental age in children up to 10-13 years with the help of the Cameriere formula modified by us. The research is based on the detection of physiological changes (the rate of formation of the roots) in the permanent teeth of children using the X-ray method.  Evaluating the results obtained by two methods, among girls and boys of the selected age group, a statistically significant strong correlation between the chronological age and the age calculated by the Cameriere method was revealed. Cameriere research has been carried out in many countries around the world and, in particular, in European countries, by implementing the general formula. Children in the period of occlusive bite remain the most critical in terms of age and, therefore, the determination of the correct time for dental interventions. In this age group, the development of permanent teeth passes through different stages and depends on many factors of the environment, genetic, geographical and food factors. The process of teething also affects many local factors, such as space and space for a permanent tooth in the dental artery and the loss of temporary precursors. Even with a large number of factors affecting the eruption and formation of permanent teeth in children, this method showed high accuracy and independence. In order to assess the Cameriere method among the children under study and its further practical application, a comparison was made between the age obtained using this methodology and the chronological age of the children under study in different age groups, both among boys and girls. Analyzing the obtained data, it was found that the mean of chronological age among the studied boys aged 10-11 (n = 14) was 11.02 ± 0.59 years, and the Cameriere method was 10.63 ± 1.03 years.  Student's assessment did not reveal a significant difference between the data (p = 0.22) for the age group of 10-11 years.  Further analysis among the studied boys revealed that in the age group 12-13 years the average chronological age was 12.94 ± 0.49 years, and the age was determined by the Cameriere method 12.59 ± 0.63 years, and no significant difference was established between them  (p = 0.14). The results of the studies have shown the suitability of the Cameriere formula modified during the process, based on the assessment of open tops and the number of teeth with completed root formation as a marker for the physiological development of the child and one that can be used to determine the child's age.Since studies had a limited age range on a particular sample of dental patients, further studies should evaluate the utility of this method in a larger sample of children in the extended age range of the given region of Ukraine and, if possible, adjust the formula we modified for the stability of the averaged indicators in different samples by age and sex.